Spirometric reference equation in men from 2 regions of northern Peru located between 0 and 100 meters above the sea level: Cross-sectional study - Pretell Cabrera, Miguel Angel (2023)
Objective: Determine the spirometry reference values and formulate an equation to predict spirometric values in the economically active population (EAP) in regions with an altitude of 0-100 m.a.s.l. Materials and Methods: Study participants were selected considering the study selection criteria. Information was collected on the variables considered in the study: Forced Vital Capacity (FVC) and Forced Expiratory Volume in the first second (FEV1), sociodemographic data and anthropometric measurements. The sample was divided into 2 groups to be able to formulate the reference equation and to assess its reliability in a validation subgroup using intraclass correlation tests, Student's t-test for paired samples, and Bland-Altman plots. Results: 1052 male participants were selected. The normal ranges for FVC and FEV1 calculated were FVC 3.48 – 5.47 and FEV1 2.83 – 4.41. Using multiple linear regression, the following formulas were obtained: FVC = 2.206 – 0.131 (Geographic Altitude) – 0.014 (Age) + 0.045 (Height) and FEV1 = 1.589 – 0.08 (Geographic Altitude) – 0.015 (Age) + 0.033 (Height). In the reliability analyses, a statistically significant difference was found in the means between the values predicted by the equation and the real values, although the Bland-Altman plots did not show a significant bias and the intraclass correlation coefficients (FVC- ICC: 0.69; FEV1-ICC: 0.70) were within an adequate range. Conclusions: The developed FVC and FEV1 equations allow adequate prediction of spirometric values in male PEA of the regions included in the study.